2020
DOI: 10.29252/wjps.9.3.290
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Double Lateral Osteotomy and Asymmetric Dorsal Hump Reduction in Correction of Crooked Nose

Abstract: BACKGROUND Several methods have been introduced to correct crooked nose during rhinoplasty. This study aimed to compare the final shape of nasal pyramid as well as patients’ satisfaction of the outcomes in two different rhinoplasty techniques. METHODS Participants in this study underwent rhinoplasty with two different techniques of double lateral osteotomy in comparison with asymmetric dorsal hump reduction using rasp. Ninety patients were allocated in two groups by a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The creation of two levels of movement decreases tension and achieves a more stable closure of the open roof. This was recognized also by Tabrizi et al who showed the long-term effectiveness of double lateral osteotomy in the correction of crooked noses compared to asymmetric dorsal hump reduction and ascribed it to a more reliable relieving of tension vectors in the deviated nose [15]. Parkes et al illustrated a technique of double lateral osteotomy in which they performed the second osteotomy at a higher level, along the path of less resistance, anteriorly and superiorly to the thick part of the maxillary process inside the nasal wall [16].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The creation of two levels of movement decreases tension and achieves a more stable closure of the open roof. This was recognized also by Tabrizi et al who showed the long-term effectiveness of double lateral osteotomy in the correction of crooked noses compared to asymmetric dorsal hump reduction and ascribed it to a more reliable relieving of tension vectors in the deviated nose [15]. Parkes et al illustrated a technique of double lateral osteotomy in which they performed the second osteotomy at a higher level, along the path of less resistance, anteriorly and superiorly to the thick part of the maxillary process inside the nasal wall [16].…”
Section: Discussionmentioning
confidence: 70%
“…Despite the growth of instruments used and techniques of osteotomy, there is not any unique accepted approach. Some of the more critical aspects are represented by the level and the direction of the osteotomy line, the possible comminution of the fracture, the surgical trauma to soft and bony tissues and the degree of the reduction in the anterior part of the nasal cavity, which may determine airflow obstruction [11,14,15]. Monolateral double osteotomy has been employed for a long time by the authors in the management of severe deviation of the nasal pyramid [3]; however, their wide experience in crooked noses led them to consider bilateral double osteotomy as a more effective way to reshape the curvature of both nasal walls.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 How to effectively restore the nasal structure and mechanical balance through surgical treatment is still a difficult problem for clinical surgeons. To date, although various surgical techniques for crooked nose have been reported by numerous experienced surgeons, such as double lateral osteotomy, 3,4 extracorporeal septoplasty, 5 reconstruction, and spreader grafts, 6 there are still cases of postoperative recurrence and unsatisfactory results. In conclusion, the main surgical approaches for crooked nose correction include the open external approach and closed endonasal approach.…”
mentioning
confidence: 99%